Analysis of Game Situations in the Design of Tasks in Training Basketball - Moreno-Ariza, José M. (2023)
Introduction: Currently, knowing how to conduct training activities is essential to optimize player training. Therefore, one of the strategies most used by coaches to optimize the training process is to modify the number of players (Game Situation). Purpose: The objective of the study was to analyze the teaching-learning process of a school-age basketball coach, as well as to know the association between the Game Situation and the Pedagogical, External Load, and Organizational variables used that influence the design of tasks. Method: For this, a total of 20 training sessions consisting of 100 tasks, recorded through the Comprehensive System for the Analysis of Training Tasks, were analyzed. A descriptive and inferential analysis was conducted between the variables raised in the research in relation to the Game Situation. Results: The results demonstrated a significant relationship between the variables analyzed with the Game Situation. The way the players are grouped during the development of the training tasks conditions the results of the rest of the variables that define a training task at a pedagogical, organizational, and external load level. Conclusion: These pieces of evidence vindicate the importance of knowing the factors that influence training tasks. In addition, the results show that there are differences in the use of game situations depending on the rest of the variables used.